De agrónomo a economista agrícola: Un derrotero intelectual - Marcos Gallacher (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
– This paper summarizes some of the milestones involved in the road leading "from Agronomist to Agricultural Economist". Personal anecdotes are presented, as well as aspects of professional work undertaken. In relation to this, selected results of research work related to the agricultural firm in Argentina are summarized. Resource productivity, efficiency and returns to scale are some of the topics analyzed.
Keywords: Q10; Q12; Q15; 330